2022
DOI: 10.1177/09749101221100637
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Customs Tax Evasion in Ethiopia: The Effect of Trade Tax, Law Enforcement, and Product Characteristics

Abstract: Low-income African countries face significant customs tax evasion due to undervaluation and smuggling of imports by registered traders. This study uses trade policy, law enforcement, product misclassification, and product differentiation to examine customs tax evasion in Ethiopian imports from Kenya. Using “missing imports” data disaggregated at the harmonized system 6-digit level, the econometric model employs the trade gap as a measure of evasion. This study seeks to explain two types of evasion: undervaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Moreover, the role of tax treaties in spurring cross-border investment in securities has been highlighted as a factor in global governance and credible commitments (Johnson, 2018). Case studies of successful international tax cooperation initiatives can be observed in the context of reducing evasion by judiciously lowering tariffs and enforcing the law at the border (Tadesse, 2022). Furthermore, the impact of tax amnesty programs on reducing cross-border tax evasion, as evidenced in Indonesia, provides insights into the relationship between tax amnesty and cross-border tax evasion (Purba et al, 2022).…”
Section: International Cooperation and Coordinationmentioning
confidence: 99%
“…Moreover, the role of tax treaties in spurring cross-border investment in securities has been highlighted as a factor in global governance and credible commitments (Johnson, 2018). Case studies of successful international tax cooperation initiatives can be observed in the context of reducing evasion by judiciously lowering tariffs and enforcing the law at the border (Tadesse, 2022). Furthermore, the impact of tax amnesty programs on reducing cross-border tax evasion, as evidenced in Indonesia, provides insights into the relationship between tax amnesty and cross-border tax evasion (Purba et al, 2022).…”
Section: International Cooperation and Coordinationmentioning
confidence: 99%
“…For instance, Kenya faces significant challenges in differentiating legal tax avoidance from illegal tax evasion, with a substantial proportion of registered companies not fulfilling their tax obligations, pointing to potential tax evasion practices [ 6 ]. Similarly, in Ethiopia, tax evasion manifests through underreporting income, inflating business expenses, and smuggling, necessitating the adoption of more sophisticated tax administration systems and rigorous enforcement strategies [ 44 ]. In Rwanda, tax evasion not only impacts revenue collection but also undermines public infrastructure and widens income inequality, necessitating reforms in tax policy and administration [ 45 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Taxpayers develop egoist behavior by evading taxes and preparing falsified documents based on the direction of some corrupted tax experts. In that instance, tax evaders engaged in malpractices; the poor moral (selfish) person has a chance to take advantage of the egoists purposefully ( Frecknall-Hughes et al, 2017 ; Tadesse, 2022 ). Taxpayers’ psychological egoism always stands for the benefit of self-interest.…”
Section: Literature Reviewmentioning
confidence: 99%